Failure to launch : a tour of ill-fated futures - McDonald, Kel; Mardikian, Hye (Iron Circus Comics, 2024)
A collection of short comics relating some of history's most notable failures, mistakes, botched inventions, and unfulfilled dreams.--Publisher.